If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -3 = 13 + -43 Reorder the terms: -3 + 3x = 13 + -43 Combine like terms: 13 + -43 = -30 -3 + 3x = -30 Solving -3 + 3x = -30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 3x = -30 + 3 Combine like terms: -3 + 3 = 0 0 + 3x = -30 + 3 3x = -30 + 3 Combine like terms: -30 + 3 = -27 3x = -27 Divide each side by '3'. x = -9 Simplifying x = -9
| 6x+33=13x-43 | | 16x^2-4y^8= | | 5x+13=6y | | 3x+x+90=180 | | 13x+9y=14 | | 3+4x=3x-11 | | 15x+2+6x+74=180 | | 7x=4x+6x | | -25+6x=5y | | 4x-0.3=x | | 2x+21=x^2+9x+33 | | 2sin^3x-sinx=0 | | 10x+5+35=90 | | g(n)=2n-1 | | 15=(1*x+3)+(3*x) | | 4x+5(2x-3)=55 | | 5(6/x)-8=4 | | m=4*20+2*5 | | 4x+27-2x=133 | | 3x+93=360 | | 2(6.5-1.5y)+3y=13 | | 4x+5(3x-17)=48 | | 2x-x+10=72 | | 2c+3c=30 | | 3-7(2-x)=5-4x | | 6x^2-18=12 | | 12x+1=5x-11 | | 4+2=3y-5 | | 65/39=52/x | | 5x-90=15 | | (x*x)+3=x(x+1)+2+2 | | 1234671234=2x+5y+18e+757547g |